Pediatric Multisystem Inflammatory Syndrome in Children as a Challenging Problem for Pediatric Surgeons in the COVID 19 Pandemic—A Case Report - Jurkiewicz, Beata; Szymanek-Szwed, Magdalena; Hartmann, Piotr; Samotyjek, Joanna; Brędowska, Eliza; Kaczorowska, Joanna; Wajszczuk, Ewa; Twardowska-Merecka, Martyna; Cybulska, Joanna (Frontiers in Pediatrics, 2021)
The first cases of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection were identified at the end of 2019 and, in the next few months, coronavirus disease (COVID-19) spread throughout the world. Initially, it was believed that this disease mainly affected elderly individuals with comorbidities, in whom respiratory failure often occurs. It was believed that children fell ill from the infection more often, although the course of infection in the vast majority of pediatric cases has been asymptomatic or mildly symptomatic. In April and May 2020, the first report of a rapidly progressing disease, similar to Kawasaki syndrome, was found in children who had been infected with SARS-CoV-2. Shortly thereafter, children with symptoms of pediatric inflammatory multisystem syndrome (PIMS-ST [temporally associated with SARS-CoV-2 infection]) began presenting to pediatric hospitals around the world. The syndrome has a mortality rate of up to 2%. Symptoms of PIMS-TS include those that may suggest the need for surgical treatment (severe abdominal pain with the presence of peritoneal symptoms, ascites, high levels of inflammatory markers, intestinal inflammation, and appendages revealed on ultrasound examination). However, there are few reports addressing surgical cases associated with this condition. The authors present a case involving an 11-year-old boy who was admitted to hospital with severe abdominal pain and underwent surgery for symptoms of peritonitis and was diagnosed with PIMS in the postoperative period. Due to the large number of illnesses caused by SARS-CoV-2 infection in recent months, the diagnosis of PIMS-TS/MISC should be considered in the differential diagnosis of acute abdominal symptoms, especially in atypical courses and interviews indicating exposure to SARS-CoV-2.